Government Finance and the Demand for Money—The Relation between Taxation and the Acceptability of Fiat Money. (28th September 2015) - Ott, Mack; Tatom, John A.
Abstract : Requiring taxes to be paid in domestic money provides a valuable characteristic for a state's money. In the case of a state's fiat money, it is the foundation for money demand and hence to the development of a financial system built around state money. Except for relatively highly taxed countries, where taxes may encourage tax avoidance and holding bank deposits, the level of taxation is a positive factor boosting financial development. Granger causality tests for 65 countries over the past half‐century examine the relationship between money and government finance. Except for the low‐income countries, where there are only five with adequate data, the causal relationship between taxation and money demand is generally supported in the 60 countries making up the three higher income groups.